Reimagining Arabic Imlā’ Instruction in the Digital Era:A Systematic Review of Mobile Learning Innovations - Yanti Kusnawati; Latifah Latifah; Ade Miswandono; AHMAD LUTFI (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This study conducts a systematic literature review (SLR) guided by the PRISMA framework to investigate the effectiveness of mobile learning applications in improving Imlā’ (Arabic orthographic accuracy) within Arabic Language Education. Twenty-five peer-reviewed studies were analyzed to evaluate how mobile-based platforms—such as Al-Quran.info, Memrise, Quran Companion, and Learning Management Systems (LMS)—support the acquisition of essential orthographic features, including tasydīd, harakāt, hamzah usage, and syntactic coherence. The review reveals that mobile learning technologies, through automated exercises, instant feedback, handwriting simulations, and adaptive scaffolding, significantly enhance students’ writing accuracy, learning motivation, and accessibility to instructional content, particularly in distance and blended learning environments. The findings further highlight the importance of aligning mobile learning tools with curriculum standards, promoting inclusive and accessible design, and strengthening educators’ digital pedagogical competencies. By integrating linguistic pedagogy with emerging mobile technologies, this study contributes to the advancement of Mobile-Assisted Language Learning (MALL) in non-Western and multilingual educational contexts. The review also identifies the need for longitudinal and large-scale empirical studies to evaluate the sustainability, scalability, and long-term instructional impact of mobile-assisted Imlā learning.